Sistotremastrum chilensis (Trechisporales, Basidiomycota), a new species from Chilean Patagonia - Telleria, M. Teresa; Dueñas, Margarita; Martín, María P. (Phytotaxa, 2014)
Sistotrematrum chilensis sp. nov. is described and illustrated on the basis of morphological and molecular data. Specimens of this corticioid fungus were collected in Huinay Reserve, in the Valdivian temperate rainforest of the Chilean Northern Patagonian region. Affinities with other species of the genus are discussed.Sobre la base de datos morfológicos y moleculares se describe e ilustra la especie nueva Sistotremastrum chilensis. Los especímenes de este hongo corticioide se recolectaron en la Reserva de Huinay, en el bosque húmedo valdiviano de la región chilena del norte de Patagonia. Se discuten las afinidades de esta especie con las del resto del género.